2019
DOI: 10.1155/2019/6765803
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Diet with Fish Oil on Oxidative Stress and Inflammatory Response in Sow and New-Born Piglets

Abstract: Pregnancy is an oxidative stress and immune challenge for the mother. Fish oil is rich in EPA and DHA, which can partly inhibit aspects of inflammation and restore antioxidant capacity. In the present study, we investigated the effect of maternal diet with fish oil during the late gestation period on oxidative stress and inflammatory response in sows and their progenies. Twelve second-parity sows were allocated equally into two groups. Sows were fed either the soybean oil diet (SD) or soybean oil+fish oil diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
1
10
0
3
Order By: Relevance
“…Prolongation of gestation, by a lesser susceptibility to preterm parturition, would increase the size and weight of newborns in pregnancies at risk of preterm delivery. The same pattern has been described in sheep models [ 37 , 38 ], and in some studies in pig models when they were given fish oil [ 39 , 40 ]. However, we didn’t find evidence in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Prolongation of gestation, by a lesser susceptibility to preterm parturition, would increase the size and weight of newborns in pregnancies at risk of preterm delivery. The same pattern has been described in sheep models [ 37 , 38 ], and in some studies in pig models when they were given fish oil [ 39 , 40 ]. However, we didn’t find evidence in the current study.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, even during lactation, the drastic catabolism and anabolism due to milk synthesis also can further contribute to metabolic disorders and in ammatory responses in sows [4,5]. Long-term exposure to in ammation may, in turn, induce poor health status or even diseases [6]. Therefore, it is necessary to develop strategies to alleviate in ammatory responses and metabolic disorders in sows, especially during late gestation and lactation.…”
Section: Introductionmentioning
confidence: 99%
“…Marianne et al (2018) reported that supplementation of DHA in piglets can signi cantly reduce the oxidative stress response caused by lipid peroxidation [28]. Although there is no report about the effect of dietary sh oil on the mRNA expression of antioxidant enzyme in the livers of piglets, placental antioxidant system has a proper capability to compensate for the oxidative stress through increasing gene expression of antioxidant enzymes in placenta [8,29,30]. We postulated that hepatic antioxidant system of piglets may also have an adaptive response to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences from animal models indicate that LPS-induced acute liver injury is caused by a variety of factors including in ammation, oxidative stress and lipid metabolism disorders. In our previous study, the supplementation of sh oil in sow diet was associated with longer gestation, alleviate oxidative stress in sows on farrowing day and modulate in ammatory response in sows and their offspring [8]. As mentioned above, we hypothesized that the maternal diet with sh oil could change the in ammatory response of the sows and potentiate the resistance for in ammation in the piglets suckling sh oil supplemented sow under the stimulation of immune stress.…”
Section: Introductionmentioning
confidence: 90%